La demopsicología de Giuseppe Pitrè, la modernidad y el siglo XX : visiones apocalípticas - Maurizio Coppola (Amnis)
The work of Sicilian scholar Giuseppe Pitrè is closely linked to the historical and cultural conditions of 19th century Italy. However, the rapid social and political transformations at the turn of the nineteenth and twentieth centuries led Pitrè to rethink his understanding of folklore and, above all, the relationship between Sicily and the rest of the country. In this article, an attempt is made to highlight how some of Giuseppe Pitrè's last writings lead one to reflect on the apocalyptic link that folklore studies have woven with the concept of modernity, introduced in particular by positivist currents. Far from a schematic opposition between tradition and modernity, Pitrè elaborates a new conception in which the ancient and the new dialogue in a complementary relationship. This view is close to some interpretations on folklore developed in Europe in the same period.